Strengthening Financial Accountability through Administrative Governance Reform: Capacity Building for BUMDes Administrators in Bacan - Suriana AR Mahdi; Rusman Soleman; Septy Indra Santoso; Meliana; Mahardika Catur Putriwana Malik (PT Keberlanjutan Strategis Indonesia, 2026)
Village-Owned Enterprises (BUMDes) are strategic policy instruments designed to promote village economic independence, increase village original income, and optimize the sustainable use of local potential. This community service program aims to analyze the implementation of administrative governance reforms to strengthen the financial accountability of Village-Owned Enterprises (BUMDes) in Bacan through a capacity-building approach. The main problems faced by BUMDes are weak administrative systems and limited managerial capacity in financial recording and reporting. The community service method uses a participatory approach that involves training and mentoring BUMDes managers. The results of the community service program indicate that administrative governance reforms contribute significantly to increasing BUMDes financial transparency and accountability. This community service program emphasizes the importance of strengthening institutional capacity as an initial strategy in realizing professional and sustainable BUMDes. The key findings of this service demonstrate that prior to the intervention, weaknesses in BUMDes' financial accountability were not solely due to limited capital or business scale, but rather to the low quality of administrative governance and the human resource capacity of managers.